Polynomial Decay Rate for a Coupled Lamé System with Viscoelastic Damping and Distributed Delay Terms - Nadjat Doudi; Salah Mahmoud Boulaaras; Ahmad Mohammed Alghamdi; Bahri Cherif (Journal of Function Spaces)
In this paper, we prove a general energy decay results of a coupled Lamé system with distributed time delay. By assuming a more general of relaxation functions and using some properties of convex functions, we establish the general energy decay results to the system by using an appropriate Lyapunov functional.